MATHEMATICAL MODEL OF OSCILLATORY WATER METABOLISM OF THE BRAIN - E. P. Titovets; L. P. Parkhach; E. V. Basiakova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A mathematical model of brain water metabolism is presented. The model takes into account the latest clinical and experimental data on cerebral fluid exchange. The model makes it possible to assess, on quantitative bases, the cerebral water metabolism and its conclusions might have clinical implications.